SrBaSiO4:Eu2+ phosphor: a novel application for improving the luminous flux and color quality of multi-chip white LED lamps - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (Institute of Advanced Engineering and Science, 2020)
This paper described in detail the chromatic homogeneity and luminous flux influences in producing better quality white LED devices with various phosphor layers (MCW-LEDs). The method is to let Eu2+-activated strontium–barium silicate (SrBaSiO4:Eu2+) mixed with their phosphor compounding, which results in notable impact on lighting performance. The increase in concentration of yellow-green-emitting SrBaSiO4:Eu2+ phosphor also promotes the color performance and lumen output of WLED devices at high correlated color temperature around 8500K. This is the first time this approach is applied and it results can be utilized for better understanding of optical properties interaction with phosphor materials. Although SrBaSiO4:Eu2+ receives many positive responses, we still need to limit it concentration for high SrBaSiO4:Eu2+ concentration is detrimental to CQS. The appropriate choice of concentration and size of SrBaSiO4:Eu2+ is the principal factor to decide the performance of MCW-LEDs.